Physicochemical characterization and antioxidant activity of polysaccharides from Chlorella sp. by microwave-assisted enzymatic extraction - Peng, Hao; Xv, Xiangjin; Cui, Xiangwei; Fu, Yongxiang; Zhang, Shuqi; Wang, Guanhao; Chen, Xue; Song, Wenlu (Frontiers in Bioengineering and Biotechnology, 2023)
Microwave-assisted enzymatic extraction (MAEE) was used for the separation of polysaccharides from micro-Chlorella. The extraction condition of MAEE was optimized by Box-Behnken design and response surface methodology. Results showed that the optimal condition for the extraction of Chlorella sp. crude polysaccharides (CSCP) was at 50 o C for 2.3 h with 380 W of microwave power and 0.31% of enzyme dosage. Under the optimal extraction condition, the extraction yield of CSCP reached 0.72%. Similarly, the α-amylase modification conditions of the CSCP were also optimized, in which the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging rate was used as the response value. The scavenging rate of DPPH free radicals was 17.58% when enzyme dosage was 271 U/g at 51 o C for 14 min. Moreover, the enzyme-modified CSCP presented a typical heteropolysaccharide mainly including glucose (48.84%), ribose (13.57%) and mannose (11.30%). MAEE used in this work achieved a high extraction yield of CSCP, which provides an efficient method for the extraction of CSCP from Chlorella sp.